Використання віртуального ультразвукового дефектоскопу для контролю зварних швів - Bohachev, Ihor; Sozonov, Stanislav (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
The magnetostrictive method of ultrasonic flaw detection has certain advantages over other methods of non-destructive testing: the ability to control objects with complex geometry, the ability to control objects in dry contact of the transducer with the object, the ability to control objects at high temperatures and in conditions of difficult access to the controlled area, etc. This work aims to verify the possibility of using and developing a methodology for inspecting welds using an existing virtual ultrasonic flaw detector with small-aperture magnetostrictive transducers. The National Instruments LabVIEW graphical programming environment was chosen as a platform for implementing computational algorithms in the form of application software.